2003
DOI: 10.1091/mbc.e02-06-0317
|View full text |Cite
|
Sign up to set email alerts
|

Myo3A, One of Two Class III Myosin Genes Expressed in Vertebrate Retina, Is Localized to the Calycal Processes of Rod and Cone Photoreceptors and Is Expressed in the Sacculus

Abstract: The striped bass has two retina-expressed class III myosin genes, each composed of a kinase, motor, and tail domain. We report the cloning, sequence analysis, and expression patterns of the long (Myo3A) and short (Myo3B) class III myosins, as well as cellular localization and biochemical characterization of the long isoform, Myo3A. Myo3A (209 kDa) is expressed in the retina, brain, testis, and sacculus, and Myo3B (155 kDa) is expressed in the retina, intestine, and testis. The tails of these two isoforms conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
84
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 68 publications
4
84
1
1
Order By: Relevance
“…To test these possibilities, we examined all coding exons of MYO3A (strong expression in calycal process of retinal photoreceptors; ref. 8) and MYO15A (interacts with the PDZD7 homolog whirlin; ref. 9) by direct sequencing of patient U329-1.…”
Section: Figurementioning
confidence: 99%
“…To test these possibilities, we examined all coding exons of MYO3A (strong expression in calycal process of retinal photoreceptors; ref. 8) and MYO15A (interacts with the PDZD7 homolog whirlin; ref. 9) by direct sequencing of patient U329-1.…”
Section: Figurementioning
confidence: 99%
“…A functionally important protein overlapping vision and hearing/balance is class III myosin (Dose et al, 2003, Walsh et al, 2002. In Drosophila, the homologous protein, called NINAC, interacts with multiple components to organize the phototransduction machinery into a signaling complex (Wes et al, 1999); NINAC is also responsible for a recessive retinal degeneration in the fly.…”
Section: A Paxb-like Gene Was An Ancestral Regulator Of Lens Crystallmentioning
confidence: 99%
“…Both isoforms are localized to actin bundle-based structures in sensory cells, including the calycal process of photoreceptors (2,6,7) and the stereocilia of inner ear hair cells (8). MYO3A and -3B are proposed to play a role in maintaining the length of the actin-bundled structures (9,10).…”
mentioning
confidence: 99%
“…Early studies found that class III myosins are not only expressed in the inner ear and retina but also in brain, intestine, and testes (2). Recently, modifications in the MYO3A gene were found to be associated with bladder and colon cancer and may be a risk factor for anxiety disorders.…”
mentioning
confidence: 99%